Happy but Unequal : Differences in Subjective Well-Being across Individuals and Space in Colombia - Burger, Martijn (World Bank, Washington, DC, 2021)
Despite being on average a relatively happy country, Colombia has a high level of inequality in subjective well-being. Using Gallup World Poll data for the period from 2010 to 2018, this paper tests the direction and strength of association of a range of objective and subjective factors with subjective well-being and explains differences in subjective well-being across individuals and space. The perceived welfare of the average Colombian is mainly influenced by conditions and expectations related to economic opportunities and education. However, quantile regressions, reveal substantial differences in the domains that matter to those at the bottom and top of the experienced welfare distribution. Standard-of-living improvements, housing affordability, and civic engagement matter more to the most fortunate top 20 percent, while having education, a job, sufficient income, economic security, and digital connectivity are much more strongly associated with the well-being of the bottom 20 percent. The life domains that matter more to the unhappiest respondents also explain the majority of the spatial differences in perceived welfare between residents in urban and rural areas as well as core and peripheral regions. Policy actions aimed at closing the gaps in these areas have the potential to increase well-being and reduce inequality in Colombia.